A review on power transformer failures: analysis of failure types and causative factors - Abdugaffar Ugli, Abdullaev Abduvokhid; Zokirovich, Tuychiev Zafarjon; Kamolovich, Jabborov Tulkin; Khamidjon Ugli, Kobilov Mirodil; Zukhriddin Ugli, Najmitdinov Zikrillo; Ziyodulla Ugli, Sharipov Mukhriddin (Institute of Advanced Engineering and Science, 2025)
This article analyzes power transformers and their components, types of damage, factors causing them. The advantage of this review article is that it was initially conducted a theoretical analysis based on published articles on power transformer damage in recent years. Then a statistical analysis was carried out on damaged power transformers in real condition. In the theoretical analysis, the articles published in the databases in recent years were first identified by keywords, and then sorted according to their relevance to the topic. A statistical examination of the damaged power transformers was performed utilizing the theoretical approach. According to the results of the analysis, damage to power transformers in 6(10) kV networks occurs mainly in 100 kVA, 160 kVA and 250 kVA power transformers. One of the factors that cause the power transformer to fail is the irregular implementation of restrictions on the power supply to electrical consumers. And these failures mainly damage the windings of the power transformer. We hope that the materials in this analytical article will serve as a crucial resource.